Strategi Humanisasi Ilmu-ilmu Keislaman dalam Pandangan Muhammad Abid al-Jabiri - Zulfa, Faizatuz; Abdillah, Junaidi (Lembaga Yasin AlSys, 2023)
Al-Jabiri's renewal thinking project focuses on the epistemological critique of traditional Arab-Islamic scientific framework. The political background of the formulation process and the structure of Islamic-Arabic logical reasoning, and the entire working mechanism of the functional language of Arabic thought. The purpose of this study is to find out the humanization strategy for Islamic sciences which is focused on the thoughts of Muhammad Abid al-Jabiri. This study uses the literature method and data as references from scientific journals, research results and also books that are relevant to the discussion. The results of this study indicate that according to Al-Jabiri, Arabic logical reasoning can be classified into: three, namely bayānī, burhānī and 'irfānī. Of the three epistemologies that are interesting to inject into the humanization of Islamic sciences is the burhānī epistemology. Because if you use bayānī epistemology it will not be suitable because it is only based on the text. It is hoped that this spirit of humanization will enable Islamic sciences to be able to solve the increasingly complex problems of the people. humanization, especially the humanization of education is needed in order to educate the life of the nation and have noble character. Furthermore, a social life will be formed which is accompanied by the spirit to develop one's own potential to achieve happiness and safety both in this world and in the hereafter.